Body. Breath. Text. Freedom: an investigation of concurrent training in Linklater voice and the Suzuki actor training method. Issue 1 (2nd January 2021) - Loth, Jo; Pensalfini, Rob
Abstract : The Suzuki actor training method and Linklater vocal training techniques are often seen as being completely antithetical. Despite, or perhaps because of, these contrasts, many actor training institutions teach the approaches concurrently. What happens when actor training methods originating from diverse cultural, artistic and philosophical traditions are taught side by side? The challenge of combining Suzuki and Linklater approaches has been explored by Robyn Hunt, Steve Pearson and Judith Shahn between 1992 and 2006 in the Professional Actor Training Program at The University of Washington's School of Drama. Hunt and Pearson's teaching included their adaption of the Suzuki actor training method, while Shahn taught Linklater voice, Speech, Dialects and Shakespearean Text. This article examines potential synergies and conflicts between Suzuki and Linklater training through a review of the available literature, alongside interview material from Hunt, Pearson and Shahn. The approaches are explored through the key concepts of Body, Breath, Text and Freedom, with a focus on laying foundations for future integrations of these techniques.